Clinicopathological analysis of expression of enhancer of zeste homologue 2 in canine mammary carcinoma - Ren Xiaoli; Fan Yuying; Li Yongqi; Shi Dongmei; Liu Yun (Journal of Veterinary Research, 2022)
Enhancer of zeste homologue 2 (EZH2) is the human homologue of Drosophila zeste gene enhancer. The aim of this study was to determine the expression of EZH2 in canine mammary carcinomas (CMCs) and its relationship with clinicopathological features.